Protocol of nutritional perioperative assistance in a general surgery service at Guilermo Almenara Irigoyen hospital, Lima - Peru - Araujo, Gustavo (1996)
From January 1995 to February 1996 in the Department of Surgery at Guillermo Almenara Irigoyen Hospital (General Surgery Service N° 5) we resolved to prepare a protocol of assessment and/or nutritional support in patients who are awaiting for surgery or who recently has undergone surgery. Our porponse is to decrease the morbimortality rate. After several work meetings, we resolved to offer this protocol for its aplication, as well as evaluation and follow up of the patients.